2019
DOI: 10.1080/03630242.2017.1421285
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between women’s characteristics and herbal medicines use during pregnancy

Abstract: The use of herbal medicines (HM) has been increasing worldwide. This cross-sectional study investigated the prevalence of and characteristics related to use of HM among 320 pregnant women. Participants were admitted to Mazandaran-based hospitals' postnatal wards from March to June 2015. Data were collected via a self-report questionnaire, including herbs used during pregnancy and demographic, socioeconomic and pregnancy-related factors. Nearly half (48.4%) of the women reported taking one or more HM during pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…This rate is significantly high compared with other similar studies conducted in other countries, such as Kenya, India, Oman, Palestine, Egypt and Taiwan [ 16 , 36 , 38 , 47 , 48 ]. These variations in prevalence could be associated with differences in the study design and/or sample dynamics [ 49 ], and also to the existence and enforcement of laws governing the marketing of medicinal plants, which also varies between countries [ 42 , 50 ]. The difference in socio-demographic and cultural factors also play a role in the number of women who use MPs [ 49 ]; many studies have revealed a strong belief among women in the safety of MPs during pregnancy [ 51 , 52 , 53 ], although little scientific evidence exists on their safety [ 50 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This rate is significantly high compared with other similar studies conducted in other countries, such as Kenya, India, Oman, Palestine, Egypt and Taiwan [ 16 , 36 , 38 , 47 , 48 ]. These variations in prevalence could be associated with differences in the study design and/or sample dynamics [ 49 ], and also to the existence and enforcement of laws governing the marketing of medicinal plants, which also varies between countries [ 42 , 50 ]. The difference in socio-demographic and cultural factors also play a role in the number of women who use MPs [ 49 ]; many studies have revealed a strong belief among women in the safety of MPs during pregnancy [ 51 , 52 , 53 ], although little scientific evidence exists on their safety [ 50 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Herbal medicine use during the first trimester has been reported previously [ 40 , 43 , 55 , 58 , 59 , 60 , 61 , 62 ]. Other studies have reported that the use of medicinal plants is more common in the second trimester [ 63 ], third trimester [ 64 ] or throughout pregnancy [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies regarding the impact of peppermint on pregnancy in women were previously published [ 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 ]. Many studies pointed to the possibility of using aromatherapy, one of the types of complementary medicine, as a care option for pregnant women to minimize nausea and vomiting in early pregnancy.…”
Section: Herbal Medicines Used To Counteract Some Pregnancy-related Symptoms (Eg Nausea and Vomiting Dizziness And Headache And Memory Lomentioning
confidence: 99%
“…Of the 33 herbs, peppermint was mentioned the most (22.8% of women) [ 125 ]. In addition, a cross-sectional study of 320 Iranian women found that 48.4% of them used herbal medicines during pregnancy, of which sour orange (30.97%), peppermint (19.81%), and borage (19.46%) were the most commonly indicated [ 126 ]. Pregnant women with secondary education and from higher socio-economic classes were more likely to use herbs.…”
Section: Herbal Medicines Used To Counteract Some Pregnancy-related Symptoms (Eg Nausea and Vomiting Dizziness And Headache And Memory Lomentioning
confidence: 99%